2014
DOI: 10.14814/phy2.12252
|View full text |Cite
|
Sign up to set email alerts
|

Visuomotor deficits during locomotion in previously concussed athletes 30 or more days following return to play

Abstract: Current protocols for returning athletes to play (RTP) center around resolution of physical symptoms of concussion. However, recent research has identified that balance and cognitive deficits persist beyond physical symptom recovery. Protocols that involve testing dynamic balance and visuomotor integration have been recommended as potential tools for better understanding of length of impairment following concussion. A dynamic, visuomotor paradigm was undertaken in the current study to assess decision making in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
(96 reference statements)
2
34
0
Order By: Relevance
“…The PEMT and other AMMP tasks were designed to challenge integrated functional performance and reveal residual deficits that become evident when limited and shareable brain resources are deliberately stressed,31 but are neither diagnostic nor mechanistic. Multiple studies32, 33,34,35,36 have shown that postconcussive dual-task deficits in gait, obstacle clearance, and balance, measured in laboratory settings, persist over much longer time frames than cognitive deficits observed in single-task conditions. This type of concurrent multiple-domain testing is intended to reveal deficits in SMs that are not always evident from single-domain assessments.…”
Section: Discussionmentioning
confidence: 99%
“…The PEMT and other AMMP tasks were designed to challenge integrated functional performance and reveal residual deficits that become evident when limited and shareable brain resources are deliberately stressed,31 but are neither diagnostic nor mechanistic. Multiple studies32, 33,34,35,36 have shown that postconcussive dual-task deficits in gait, obstacle clearance, and balance, measured in laboratory settings, persist over much longer time frames than cognitive deficits observed in single-task conditions. This type of concurrent multiple-domain testing is intended to reveal deficits in SMs that are not always evident from single-domain assessments.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that trekking poles affect walking speed [7,9,20], the control of speed could interfere the aim of this study. During a usual locomotion, human reduces and optimizes energy cost by continuous adjustments of the walking speed, stride length, and stride frequency [23][24][25][26]. And at a preferred walking speed, there were no age and sex differences of metabolic responses [27].…”
Section: Discussionmentioning
confidence: 99%
“…To progress through these stages, the athlete must remain symptom free. 1,4,5 However, recent research has identified that balance dysfunction and cognitive deficits persist well beyond the physical symptoms of the recovery process. 5 The length of recovery following a concussion varies, lasting anywhere from 1 week to several months.…”
Section: Discussionmentioning
confidence: 99%
“…1,4,5 However, recent research has identified that balance dysfunction and cognitive deficits persist well beyond the physical symptoms of the recovery process. 5 The length of recovery following a concussion varies, lasting anywhere from 1 week to several months. 6,7 Risk factors that can lead to increased recovery time include a history of 1 or multiple concussions and a greater number, severity, and duration of symptoms after the injury.…”
Section: Discussionmentioning
confidence: 99%